Prescribing pattern of antidepressant drugs in two teaching hospitals in Bangladesh - Islam, Baishakhi; Shahriar, Iram; Jannat, Tamanna (Mediscope, 2019)
As depression is a major public health problem, a drug utilization study is beneficial in clinical practice for rational prescribing and helpful for minimizing the medication errors. In our country antidepressant drugs are commonly used in treatment of depression. To obtain information regarding the prescribing pattern of antidepressant drugs in accordance with WHO prescribing indicators, a descriptive cross sectional study was carried out at psychiatry out-patient department of Sir Salimullah Medical College & Hospital(SSMCH) and Dhaka Medical College Hospital(DMCH) in Bangladesh. A total of 300 (150 in each hospital) prescriptions were analyzed by using WHO prescribing indicators and Essential Drug List of Bangladesh. Among 300 patients with major depression (64%, 58.66%), females were(53.33%, 58%) and males were (46.67%, 42%) which is commonly seen between the age group 18-27 years in DMCH and SSMCH respectively. Most commonly prescribed antidepressant as monotherapy was sertraline (58.02%, 70%). Average number of drugs per prescription was (2.24 ± 0.93, 2.12 ± 0.83). Percentage of drug prescribed by generic name and percentage of encounters with an injection prescribed was nil in both hospitals. Percentage of drugs prescribed from Essential Drug List of Bangladesh was (37.5%, 25.47%) in DMCH and SSMCH respectively. Prescribing pattern of antidepressant drugs in both teaching hospitals are almost similar in accordance with WHO prescribing indicators. Mediscope Vol. 6, No. 2: Jul 2019, Page 53-58